Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-022-10510-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to double SARS-CoV-2 mRNA vaccination in Japanese kidney transplant recipients

Abstract: Immunocompromised patients, especially those who undergo kidney transplantation, have lower antibody levels following SARS-CoV-2 mRNA vaccination. The situation of transplant treatment, such as transplant source and immunosuppressive drugs, is different in Japan than that in other countries. Therefore, it is necessary to clarify whether antibody acquisition rates differ between Japan and other countries. This retrospective study included patients with post-kidney transplant who were attending at the Nagoya Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…The trend was similar to that of healthy participants in that the highest antibody titer was obtained after the third vaccination. In kidney-transplanted patients, the results of this study revealed that the antibody-acquisition rate after the second vaccination (44.8%) was slightly higher than that reported in our previous study (31.5%) [ 16 ] and similar to that reported in other countries [ 17 , 18 ]. This may be because older adults, who are at a higher risk of severe SARS-CoV-2 infection, were prioritized for vaccination in Japan; therefore, the patients in the previous study were from an older age group than those in this study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The trend was similar to that of healthy participants in that the highest antibody titer was obtained after the third vaccination. In kidney-transplanted patients, the results of this study revealed that the antibody-acquisition rate after the second vaccination (44.8%) was slightly higher than that reported in our previous study (31.5%) [ 16 ] and similar to that reported in other countries [ 17 , 18 ]. This may be because older adults, who are at a higher risk of severe SARS-CoV-2 infection, were prioritized for vaccination in Japan; therefore, the patients in the previous study were from an older age group than those in this study.…”
Section: Discussionsupporting
confidence: 83%
“…On comparing the group that acquired S-IgG after the third vaccination with the group that did not acquire S-IgG, significant differences in BMI and eGFR were observed. This was equally true for the rate of S-IgG acquisition after the second vaccination that we previously reported [16]. Regarding BMI, low BMI was associated with failure of antibody acquisition in our transplant patient data.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We acknowledge that a small group of subjects is a limitation that prevents general conclusions and strong recommendations. However, the results of our study add supplementary information to the data obtained from other centers [ 24 , 30 , 31 ] regarding anti-SARS-CoV-2 vaccination and bring new knowledge about the immune response after such vaccination in kidney transplant patients, at the same contributing to further recommendations on how to manage these patients. The main strength of our study is the assessment of COVID-19 morbidity in kidney transplant patients after social isolation due to the pandemic.…”
Section: Discussionmentioning
confidence: 61%